Differences in dental age of small gestational age children based on the severity of enamel dental defects - Kania, Annisa Maya; Oewen, Roosje Rosita; Suwondo, Williyanti (Universitas Padjadjaran, 2010)
Small Gestational Age (SGA) is the term used for a new born baby with birth-severe below the 10th percentile on the intrauterine Lubchenco curve, due to Intra Uterine Growth Restriction (IUGR) which can cause defects of several organs such as deciduous teeth enamel. Dental age is the indicator for growth and development of the teeth that determine biological age which is more accurate than chronological age and could be determined by calcification or teeth eruption. The purpose of this study was to obtain dental age in SGA children based on the enamel defect severity level of deciduous teeth as compared to the chronological age. This study was a comparative analytic study with given sample size, conducted towards 18 SGA children aged 4-6 years old, and 21 children with Appropriate Gestational Age (AGA) aged 4-6 years old as the control group. Deciduous teeth enamel defect severity level determined by the developmental defect of enamel (DDE) score FDI modified. In order to determine the permanent teeth growth and development, the indicator was based on dental age using the panoramic radiograph with Dermijian method. The t-test was used to compare the permanent teeth dental age difference between SGA and AGA children as well as the permanent teeth dental age difference of SGA children based on the enamel defect severity level of deciduous teeth as seen in their chronological age. The result showed that there was a difference in the permanent teeth dental age between the SGA and AGA children at chronological ages of 4, ,5, and 6 years old (t count = 3,36; 2,35; and 3,49). Based on the average of permanent teeth dental age, the value of AGA children was higher than SGA children. Furthermore, it also showed that the severe score of EDS in the SGA children at the age of 4, 5, and 6 years old, their permanent teeth dental age was lower than the mild EDS (t count = 1,45). The conclusion of this study was the permanent teeth dental age in SGA children was lower than the AGA children as well as difference between the permanent teeth dental age in SGA children based on their deciduous teeth enamel defect severity, and the severe defect refered to slower permanent teeth dental age than the mild defect.